Probing Non Unitarity of Neutrino Mixing Matrix on Lepton Flavour Violation, Leptogenesis and Neutrino Oscillation Probability - Gayatri Ghosh (New Insights into Physical Science Vol. 13, 2021)
Neutrino Physics is a mature branch of science with all the three neutrino mixing angles and two mass squared differences determined with high precision. Inspite of several experimental veri?cations of neutrino oscillations and precise measurements of two mass squared differences and the three mixing angles, the unitarity of the leptonic mixing matrix is not yet established, leaving room for the presence of small non-unitarity effects. Deriving the bounds on these non-unitarity parameters from existing experimental constraints, on cLFV decays such as, we study their effects on the generation of baryon asymmetry through leptogenesis and neutrino oscillation probabilities. We consider a model where see-saw is extended by an additional singlet S which is very light, but can give rise to non-unitarity effects without affecting the form on see saw formula. We do a parameter scan of a minimal see-saw model in a type I see-saw framework satisfying the Planck data on baryon to photon ratio of the Universe, which lies in the interval, We predict values of lightest neutrino mass, and Dirac and Majorana CP-violating phase for normal hierarchy and inverted hierarchy for one ?avor leptogenesis. It is worth mentioning that all these four quantities are unknown yet, and future experiments will be measuring them. Future measurements related to Dirac CPV phase in neutrino experiments will validate or contradict some of the results presented here. Our analysis in this work only provides a benchmark for consistent works affiliated to model building.